Mediating Effect Of Subcontractor Bullying On Factors Influencing Intention To Quit - Hidzir, Nur ‘Izzati (2018)
Workplace bullying is gradually being identified as a serious problem in the work environment. Acknowledging this problem, a number of studies has been conducted to overcome this problem. However, the previous studies were focussing on different fields and industries. Only a few studies were focussing on workplace bullying in a construction project. However, studies on workplace bullying in construction projects remain scarce, particularly from the subcontractors’ perspectives. There are three objectives in this study. First, to examine the relationship of bullying factors (main contractors’ leadership, work organisation and job design and construction culture) and bullying among the subcontractors (workbased bullying and physical-based bullying) in construction projects. Second, to analyse the relationship between bullying factors (main contractors’ leadership, work organisation and work design and construction culture) and bullying among the subcontractors (work-based bullying and physical-based bullying) towards the subcontractors’ intention to quit from the construction projects. Third, to examine the relationship of bullying mediation among the subcontractors (work-based bullying and physical-based bullying) and bullying factors (main contractor leadership, work organisation and job design and construction culture) and the intention to quit. A questionnaire survey was administered to collect data among the contractors G6 and G7 (n=210) across Peninsular Malaysia. For the data analysis, Partial Least Squares – Structural Equation Modelling (PLS-SEM) was used by using the Smart PLS software.